Corporate Social Responsibility and Citizenship Behaviour: A Case Study of Dell - Aziz, Abdul; Kee, Daisy Mui Hung; Danieal, Danieal; Azmi, Mohd; Firdaus, Mohamad; Alkhalaf, Lulwa; Tripathi, Abhishek (Journal of The Community Development in Asia, 2020)
The study intends to examine the corporate social responsibility and citizenship behavior in Dell. Dell Computer Corporation was established in 1984 by Michael Dell. Dell is an American multinational corporation that specializes in computer technology. Dell introduces the concepts of selling personal computer systems directly to customers, offers build-to-order computer systems, and provides direct, toll-free technical support and next-day, on-site service. Dell has many headquarters all over the world and one of them is in Malaysia. The paper also discusses how the corporate social responsibility bring an impact to their employees in terms of their citizenship behavior. The paper concludes with some implication and recommendation.